Systematic literature reviews in teachers’ attitude on students’ performance for learning after a vaccine for Covid-19 - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
The research aims to provide knowledge about the recognition and use of faculty technologies for education lectures are responsible for developing moral character. Preliminary results were gathered from a survey offered to 182 departments of four universities. The researcher used a definition and interpretation approach for quantitative and qualitative use in this study. There were 530 lectures of 25-50 years of age (men and women). A study was conducted based on Kohlberg's theory's concept of gender identity. Findings show that technology is mostly optimistic and that universities and colleges do not have adequate technological assistance (both hardware and training). The most popular forms of technologies are the course management, laptop and web applications. The data show that, intermediately or marginally below, the departments as a whole operates in the accepting/use spectrum of technology.